2004
DOI: 10.1179/096797804x4556
|View full text |Cite
|
Sign up to set email alerts
|

Whiskerisation of polycrystalline SiC fibres during synthesis

Abstract: Whiskers of b-SiC have been produced on the surfaces of polycrystalline SiC fibres by carbothermal synthesis. The growth of whiskers occurred simultaneously with siliconisation of the carbon fibres. The chemical composition, structure and morphology of the whiskers were studied using X-ray diffraction (XRD), Raman microspectroscopy, electron energy loss spectroscopy (EELS), scanning electron microscopy (SEM) and transmission electron microscopy (TEM). It was found that the presence of silica on the surface of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 14 publications
(13 reference statements)
1
15
0
Order By: Relevance
“…The formation of SiC whiskers during the synthesis of biomorphic SiC ceramics from mineralized cellulosic preforms was reported by many authors 10,26 . In the present study, impurities from the cellulosic fabrics acted as whisker nucleation sites; at the same time silicon deposited on the carbon surface promotes the growth of SiC whiskers 27 …”
Section: Resultssupporting
confidence: 69%
“…The formation of SiC whiskers during the synthesis of biomorphic SiC ceramics from mineralized cellulosic preforms was reported by many authors 10,26 . In the present study, impurities from the cellulosic fabrics acted as whisker nucleation sites; at the same time silicon deposited on the carbon surface promotes the growth of SiC whiskers 27 …”
Section: Resultssupporting
confidence: 69%
“…Impurities from wood or sodium silicate might have acted as nucleation sites. Silica deposited on the carbon surface is known to promote the growth of SiC whiskers 21 …”
Section: Resultsmentioning
confidence: 99%
“…Vyshnyakova, Institute for Problems of Materials Science, National Academy of Sciences, Ukraine. 16 Raman spectroscopy and x-ray diffraction (XRD) studies of whiskers showed that the whiskers had beta-SiC structure. Sintered SiC disks were obtained from Saint-Gobain (Northborough, MA).…”
Section: A Materialsmentioning
confidence: 99%